2022
DOI: 10.2147/cia.s350195
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Postoperative Delirium After Cardiac Surgery with A Quick Test of Cognitive Speed, Mini-Mental State Examination and Hospital Anxiety and Depression Scale

Abstract: Purpose To evaluate if preoperative assessment with A Quick Test of Cognitive Speed (AQT) could increase the accuracy of predicting delirium after cardiac surgery compared to Mini-Mental State Examination (MMSE), and examine if a composite of variables, including cognitive function and depressive symptoms, could be useful to predict delirium. Patients and Methods Cardiac surgery was performed in 218 patients (mean age 72 years). Preoperative evaluation involved AQT, MMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 50 publications
(56 reference statements)
0
20
0
Order By: Relevance
“…Mini-Mental State Examination has been generally accepted as a simple scale to evaluate cognitive function, including 30 lists of decline symptoms totally, and lower scores represented worse cognitive condition in patients ( Segernäs et al, 2022 ). Our results showed that pre-operative MMSE scores in POD group were two points lower than those in non-POD group and were negatively associated with POD via multivariate regression analysis, which suggested that patients may have some impaired brain function pre-operatively, and thus increasing the probability to develop POD ( Pettemeridou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mini-Mental State Examination has been generally accepted as a simple scale to evaluate cognitive function, including 30 lists of decline symptoms totally, and lower scores represented worse cognitive condition in patients ( Segernäs et al, 2022 ). Our results showed that pre-operative MMSE scores in POD group were two points lower than those in non-POD group and were negatively associated with POD via multivariate regression analysis, which suggested that patients may have some impaired brain function pre-operatively, and thus increasing the probability to develop POD ( Pettemeridou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data obtained from the electronic anesthesia record included operation and anesthesia time, surgical types, drugs usage (remifentanil and sufentanil), and others. Mini-Mental State Examination (MMSE) was adopted to assess the pre-operative cognitive condition, and MMSE score of less than 27 indicated cognitive impairment ( Segernäs et al, 2022 ). Anxiety or depression was diagnosed by Hospital Anxiety and Depression Scale (HADS) ( Pais-Ribeiro et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, MMSE scores can be influenced by education, age, language, and ethnicity, with concerns also about limitations in identifying patients with mild cognitive impairment 7–9 . In addition, to the best of our knowledge, no reports exist of MMSE being highly predictive (performance exceeding 0.8 in the area under the receiver operating characteristic curve [AUC]) for POD 5,10 …”
Section: Introductionmentioning
confidence: 99%
“…Delirium is an acute organ dysfunction with mental status changes including alterations in level of consciousness, known to burden postoperative outcomes [ 2 ] and investigated in patients undergoing non-cardiac [ 3 ] and cardiac surgery [ 4 ]. Preoperative cognitive status and depression have been associated with postoperative delirium (POD).…”
mentioning
confidence: 99%
“…Preoperative cognitive status and depression have been associated with postoperative delirium (POD). Assessment scores can be influenced by age, education or ethnicity [ 4 ]. Some strategies are currently being investigated aiming at predicting and treating POD after in different settings [ 5 , 6 ].…”
mentioning
confidence: 99%